The Integration of Socio-Cultural Aspects in the English Textbooks entitled English in Mind - Muchamad Saepudin; Januarius Mujiyanto; Suwandi Suwandi (Universitas Negeri Semarang, 2022)
Language and sociocultural are inseparable and bound to each other. Language is the expression of cultural reality, the embodiment of cultural reality, and the symbols of cultural reality. The inseparability of language and culture has led researchers to investigate English language teaching taught in various cultural contexts. This study qualitative approach, in which the data were taken from an English textbook entitled English In Mind published by the Ministry of Education and Culture. The data were gathered by classifying the six sociocultural aspects (nomenclature, address terms, cultural information, cultural sites, sociocultural tradition, etiquette) and analyzed using the theory of sociolinguistics. The finding of this research, After Analyzing fourteen chapters English textbooks observed in this study show